Impact of climate change on millet yield under different fertilization levels in three agroecological zones of Niger Republic - Ali Malam Labo Mohamed; Salack Seyni; Siyabusa Mkuhlani; Abel Chemura; Babacar Faye; Suleymane Abdul Kadir; Agossou Gadedjisso-Tossou; Bindawa. Mansur. Auwalu (PLoS ONE, 2025)
The study investigates the impact of climate change on pearl millet production in Niger, focusing on projected changes in temperature and rainfall. The research uses the CERES-millet model in the DSSAT framework to simulate millet yields under three climate scenarios (SSP1–2.6, SSP3–7.0, and SSP5–8.5) for different time periods: 2015–2044, 2045–2074, and 2075–2100. Five Global Circulation Models (GCMs) with varying climate sensitive were selected for simulations these include (IPSL-CM6A-LR, MPI-ESM1–2-HR, GFDL-ESM4, MRI-ESM2–0, and UKESM1–0-LL). The CERES-Millet model was calibrated using field experiment data collected during the 2021 and 2022 rainy seasons at two locations in Niger Goungoubon (2021 and 2022) and Fandou (2022). Trials were established near irrigation facilities to ensure optimal moisture conditions, with supplemental irrigation applied whenever soil moisture dropped below field capacity. Calibration involved iterative adjustment of key genetic coefficients using observed phenological stages and grain yield to improve model accuracy. The performance of the model was then validated by comparing simulated and observed values of phenology and yield showing good agreement and confirming it reliability. The study found that rising temperatures, particularly under high-emission scenarios, lead to shortened flowering and maturity times, with more pronounced effects towards the end of the century. Additionally, changes in rainfall patterns were expected, with an increase in rainfall projected for the Sahel region. The simulations revealed a consistent decline in millet yields across most scenario, with the greatest yield losses occurring under the SSP5–8.5 scenario in the 2075–2100 period. The results highlight the significant threat that climate change poses to pearl millet production, emphasizing the need for adaptive crop management strategies.